IMPLIKATUR BERMAKNA BUDAYA SOSIAL PADA NYANYIAN RAKYAT DENGE SUKU TOBELO DI DESA WOOI KEC. OBI TIMUR - Agus Boriri (Titian: Jurnal Ilmu Humaniora, 2021)
This study aims to describe the meaningful implicatures of social culture found in the Tobelo tribe conducted in Wooi Village, East Obi District, South Halmahera Regency. The sources of data in this study are direct (primary) sources obtained by the community in Wooi Village, while indirect (secondary) sources can be obtained through books, articles, and so on from libraries or places. The results of the study prove that the implicatures contained in the folk songs of the Tobelo tribe in Wooi Village, Kec. East Obi, namely: 1) implicature type of invitation there are 7 stanzas, 2) implicature type of statement action there are 9 stanzas, 3) implicature type of Command there are 2 stanzas. It can be concluded that 1) The implicatures contained in folk songs with the Tobelo tribe in Wooi Village are invitation implicatures, statement action implicatures, and Command implicatures. 2) Implicature means that the social culture found in the Tobelo tribe in Wooi Village is an attitude of social care, friendly/communicative and peace-loving, honest, hard working and tolerant.